Dominant functional role of the novel phosphorylation site S811 in the human renal NaCl cotransporter. Issue 8 (16th March 2018) - Tutakhel, Omar A. Z.; Bianchi, Frans; Smits, Daniel A.; Bindels, Rene J. M.; Hoenderop, Joost G. J.; van der Wijst, Jenny
Abstract : The NaCl cotransporter (NCC) is essential for electrolyte homeostasis and control of blood pressure. The human SLC12A3 gene, which encodes NCC, gives rise to 3 isoforms, of which only the shortest isoform [NaCl cotransporter isoform 3 (NCC3 )] has been studied extensively. All NCC isoforms share key phosphorylation sites at T55 and T60 that are essential mediators of NCC function. Recently, a novel phosphorylation site at S811 was identified in isoforms 1 and 2 [NaCl cotransporter splice variant (NCCSV )], which are only present in humans and higher primates. The aim of the current study, therefore, is to investigate the role of S811 phosphorylation in the regulation of NCC by a combination of biochemical and fluorescent microscopy analyses. We demonstrate that hypotonic low‐chloride buffer increases S811 phosphorylation, whereas phosphorylation‐deficient S811A mutant hinders phosphorylation at T55 and T60 in NCCSV and NCC3 .NCCSV S811A impairs NCC3 activity in a dominantnegative fashion, although it does not affect plasma membrane abundance. This effect may be explained by the heterodimerization of NCCSV with NCC3 . Taken together, our study highlights the dominant‐negative effect of NCCSV on T55 and T60 phosphorylation and NCC activity. Here, we reveal a new function of NCCSV in humans that broadens the understanding on NCC regulation in blood pressure control.—Tutakhel, O. A. Z., Bianchi, F., Smits, D. A., Bindels, R. J. M., Hoenderop, J. G. J., van der Wijst, J. Dominant functional role of the novel phosphorylation site S811 in the human renal NaCl cotransporter. FASEB J . 32, 4482–4493 (2018). www.fasebj.org